Effect of Microchannel Depth on Subcooled Flow Boiling Instability and Heat Transfer - N. Shah; A. Prajapati; H. B. Mehta; J. Banerjee (Journal of Applied Fluid Mechanics)
Microchannel heat sinks (MCHS) are capable of removing exceptionally high heat fluxes through liquid-to-vapor phase transition, making them suitable for various applications, including the thermal management of high-power microelectronics. However, their commercial applicability is hindered by the flow boiling instability associated with chocking of the micro-passage as the vapor bubbles grow. The present study addresses the research gap in literature pertaining to the impact of microchannel depth on flow boiling instability in terms of amplitude of heated surface temperature and pressure drop oscillations, and their influence on heat transfer performance. Experiments are conducted using dielectric water boiling in multiple parallel microchannels with mass fluxes of 220 and 320 kg/m²s and wall heat fluxes ranging from 25 kW/m² to 338 kW/m². Two different MCHS, fabricated from oxygen-free copper substrate, were examined, each comprising 44 parallel microchannels with nominal depths of 500 µm and 1000 µm, and a consistent nominal width of 200 µm. Heat transfer coefficients were measured using an array of embedded T-type thermocouples on the substrate to measure temperature gradients. The findings reveal that increasing the microchannel depth results to a significant increase in the amplitude of wall temperature fluctuations under fixed wall heat flux conditions, which in turn diminishes heat transfer performance. Additionally, the study demonstrates a notable dependence of pressure drop on coolant flow and both microchannel sizes. This research provides new insights into optimizing MCHS design for enhanced thermal management, highlighting the critical role of microchannel depth in mitigating flow boiling instability and improving overall heat transfer efficiency.